Age-structured bioeconomic model for strategic interaction: an application to pomfret stock in the Arabian/Persian Gulf. (25th April 2020) - Ben-Hasan, A; Walters, C; Christensen, V; Munro, G; Sumaila, U R; Al-Baz, A
Abstract: When fish stocks migrate across multiple exclusive economic zones (EEZs), they compel managers to examine management at both national and international levels. A strategic interaction emerges when the fishing activity of one country impacts fishing opportunities available for other countries sharing the stock. Left unaddressed, strategic interaction could lead to overexploitation and suboptimal payoffs. Here, we develop and apply a bioeconomic model to address the competitive fishing for silver pomfret in the Arabian/Persian Gulf—a highly commercial fish stock shared between Kuwait and Iran—and evaluate biological–economic trade-offs under competition, cooperation, and country-independent management using maximum sustainable yield ( MSY ) and fishing mortality that maintain MSY ( Fmsy ) policies. When cooperation involves an equal share of the overall Fmsy or a share based on the proportion of the stock available in each EEZ, countries are expected to cooperate given the substantially higher catch, biomass, and relative profits compared to other management regimes. However, other than these two arrangements, countries would favour different regimes. Besides providing policy insights to improve the perilous status of silver pomfret, our approach could be useful in exploring alternative fishing arrangements to sustainably harvest a transboundary fish stock while maximizing average yields.